CONSEQUENCES OF COAL PROJECTS LEADING TO DISPLACEMENT OF LAND LOSERS: A PAINFUL AND DISRUPTIVE PROCESS - GUPTA, ANUP KRISHNA; DUTTA, AJOY KUMAR; BASU, RITA (IJRDO - Journal of Business Management, 2018)
For the purpose of steady and faster economic growth, plans for development in all front including industrial units appear to be important. In deciding priority concentration on viable schemes with concrete plan of action will be essential. Coal, the prime energy source will be dominating industrial front for a few decades to come, and therefore, attaching importance to new Coal Projects will gain priority. New Projects, especially in Coal sector is directly dependent on the prime   parameter-land. Land of various size is required for coal extraction either from underground, incline or opencast. With the acquisition of land for coal projects through various laws, people   associated with the land become affected–and this may cause shifting of settled people. For economic growth and in the interest of nation while new Coal Projects are essential, land acquisition and consequent effect disrupts the traditional, social system and source of livelihood of the people associated to such land. Displacement of people involuntarily may give rise to severe social, economic and environmental problem because 1) in the relocated environment productive skill of the people may be less applicable,2 ) productive asset and sources of income are lost 3) social structure may get disrupted 4) cultural identity may diminish. A balance between economical growth and protection of project affected people is the prime task before public sector coal companies.